THE LEVELLERS AND THE BIRTH OF LIBERAL POLITICAL ECONOMY. Issue 1 (2020) - Otteson, James R.
Abstract: When did liberal political theory, or perhaps liberal political economy, begin? Although many would trace their beginnings to the writings of Adam Smith, David Hume, or perhaps John Locke, in fact many of the propositions we today recognize as forming the core of liberalism were articulated in the first half of the seventeenth century by an unduly neglected group called the Levellers and their leader John Lilburne. In this essay, I first give some historical background and context to the Levellers and Lilburne. Next, I articulate several of their liberal positions, including freedom of religion, freedom of speech, and freedom of commerce and trade, and I examine their justifications for these positions, which I argue were both novel and radical. I conclude by exploring the contemporary relevance of the Levellers and argue that they should be considered as among liberalism's most important founders.